Efeito do período de conservação sobre a composição química e a concentração de micotoxinas em silagem de sorgo de planta inteira - Schumacher, Larissa Luisa (2021)
This research was conducted in order to evaluate the effect of different storage periods on fermentation profile, nutritional value, in vitro fermentation, carbohydrate fractionation, protein fractionation, anaerobic losses, and the mycotoxins in whole-plant sorghum silage (WPSS). The experimental design used was completely randomized, with four treatments (45, 90, 180, 360 days of conservation) and four replications each. The storage period affected fermentation profile, in which the lactic and acetic acids showed their maximum concentration at 218 and 163 days, respectively. Propionic and butyric acid increased linearly over time. The dry matter content reduced 0.01072 g kg-1 per day of storage, the pH peaked at 26 days, while ammonia nitrogen showed a linear increase of 0.08700 g kg-1 for each day of storage. Effluent losses increased, in the order of 0.0036 g kg-1 per day of conservation, while gas losses showed a quadratic behavior. Non-fibrous carbohydrates showed a minimum concentration at 207 days of storage. There was a decrease in the fractions CA4, CB1, CB2 and CB3, negatively affecting the glycidic content of sorghum silage as the storage time progressed. Regarding protein fractionation, PBA, PB2 and PB3 increased, while PBC decreased with storage time, thus reducing the indigestible protein portion of the silage. For the kinetic parameters, the final volume, gas production (PG) 24h, PG 48h and PG 96h presented a quadratic decreasing behavior. The degradation rate increased linearly and the time needed to reach half of the maximum gas production and DEGDM_48h linearly decreases with each day of conservation. The silo temperature showed positive linear growth in relation to the conservation period. We did not observe time effect on (P>0.05) PMS and PNDT, but there was change for PFDN with linear reduction and PPB with linear increase. FUMO and AFLA mycotoxins remained below detection limits in pre-ensiled samples and throughout the conservation period. The ZEA concentration showed a quadratic behavior, while DON linearly increased up to the 360 days evaluated. A negative correlation of DON with MS, PFDN and PNDT and positive with silo and ambient temperature was observed. ZEA was positively correlated with propionic acid, butyric acid and negatively correlated with PNDT. Two prediction models were generated, in which silo temperature and DM content accounted for 91% and 38% of the variation in DON concentration. Thus, we observe that as the storage period increases, relevant changes occur. Furthermore, the fermentation process is not able to attenuate the occurrence of DON and ZEA in the silage of the whole sorghum plant.